Ta'tsiru Al-Barnamij Al-I'dadi Fi Tahsini Al-Maharat Al-Lughawiyah Atsna Al-Waba' (Covid-19) - Irma Nur Fita Sugianto; Khizanatul Hikmah (Institut Agama Islam Negeri (IAIN) Metro, 2021)
New students at Ma’had Umar Bin Al-Khattab for girls Sidoarjo have various educational backgrounds. So that the ability to speak Arabic is also different. To solve these problems, a preparation class was formed to equalize their language skills. This study aims to determine the effect of the matriculation programs to improve the arabic language skills of new students. This study uses quantitative research methods using T-Test formula. T-Test formula is used to determine the comparison of student scores before and after taking matriculation programs. The results of this study indicate that the matriculation programs has an effect on improving the lamguage skills of each student. This difference is influenced by differences in the educational background of these students. In the matriculation program students are taught basic arabic lamguage skills such as maharah istima’, maharah kalam, maharah qiro’ah, and maharah kitabah. The existence of this matriculation programs is useful for equalizing language skills and preparing student’s language skills in order to take the lectures that will be taken.